(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
A cross-sectional study was carried out to determine the prevalence of subclinical mastitis (SCM) in the dairy farm at Shahjadpur Upazila in Sirajganj District of Bangladesh from December 2022 to December 2023. A total of 150 lactating cows was randomly selected and screened for SCM by using the California Mastitis Test (CMT). The overall prevalence of SCM at the farm level was 67.5% whereas at individual-level was 55.33% followed by quarter level (28.50%). The prevalence of subclinical mastitis was significantly higher in cross-bred cows (59.28%) compared to indigenous (40%). The cows with a daily milk yield of ≥16 L showed a higher prevalence of subclinical mastitis (69.41%). The prevalence during early lactation (£2 months) was recorded comparatively higher (59.26%). Age-wise prevalence was more prominent in ≥7-year-old cows, which was 72.09%. The prevalence of subclinical mastitis was comparatively higher (58.88%) in lactating cows that were housed with semi-paka floors compared to the muddy floor (41.18%). This study revealed the increasing prevalence with the increasing number of parities that was higher (70.00%) at ≥4th parity and lowest at 1st parity (45.00%). Descriptive statistics represented the farm demography and management status in the study area. The findings of the study may develop awareness among farmers and other stakeholders to prevent subclinical mastitis in dairy cows. Res. Agric. Livest. Fish. Vol. 11, No. 3, December 2024: 271-281